Development of a computer solution for the analysis of data within social security payment system for the colombian financial sector (Revista Cientifica Ingenio Magno, 2020)
The article shows the development of a computer solution based on a technological platform that allows online consultation of information contained in the system PILA – (Integrated Contribution Payment Form), where the payments to social security of active Colombian workers and pensioners are registered. This information could be use in the banking sector and financial institutions for decision-making. Therefore, the proposed system will provide greater access to financial services for people who have limited access to financial services due to a lack of reliable information. The proposed platform includes control modules defined as web API services that allows the administration of several services divided into modules. The modules work as micro-components of applications, which interact with each other through the Kafka messaging system (Based on a data pipeline architecture) at the integration level, operating with a resource-oriented architecture to consume services between them.
Keywords: Data Analysis; Load Balancer; Big Data; Social Security Payments; Computer Platforms; Computer Security; Web Services